METODE PMBENTUKAN AKHLAK PERSPEKTIF M. QURAISH SHIHAB - Lailatul Maskhuroh; Kurroti A’yun (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
Ibn Abbas, one of the companions of the Prophet classified the level of rasikh in understanding al Qur’an verses as four parts: first, it is able to be understood by Arabian generally based on their linguistic; second, there is no reason for them to let it; third, noone knows except scholars; and fourth, only Allah knows it. This is proof of the miracles and the truth of the prophet Muhammad SAW, one of the al Qur’an terms of language which can be accepted by the owner’s only. Besides, Muhammad’s friends who witnessed the al Qur’an descent, they knew and understood it structure and vocabulary of the language, and the context of the verses passage, so the appreciation of the al Qur’an interpretation is always needed by the Indonesian mufassir that is M. Quraish Shihab in tafsir al Misbah.